Ta’lim jarayonida talabalarning mustaqil ta'lim faoliyati ko'nikmalarini shakllantirishning o’ziga xos xususiyatlari - Qalandarov H. K. (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This article examines the independent activity of students in the educational process, the goals of independent work aimed at achieving communicative, educational goals, unique methods of organizing independent work of students in the process of creative activity, theoretical approaches. The opinions of a number of scientists and researchers and critical approaches to them are analyzed.